Clinical evaluation of glycoPEGylated recombinant FVIII: Efficacy and safety in severe haemophilia A - Giangrande, Paul; Andreeva, Tatiana; Chowdary, Pratima; Ehrenforth, Silke; Hanabusa, Hideji; Leebeek, Frank W. G.; Lentz, Steven R.; Nemes, Laszlo; Poulsen, Lone Hvitfeldt; Santagostino, Elena; You, Chur Woo; Ong Clausen, Wan Hui; Jönsson, Peter G.; Oldenburg, Johannes; for the Pathfinder™2 Investigators (Thrombosis and Haemostasis, 2017)
Turoctocog alfa pegol (N8-GP) is a novel glycoPEGylated extended half-life recombinant factor VIII (FVIII) product developed for prophylaxis and treatment of bleeds in patients with haemophilia A, to enable higher activity levels with less frequent injections compared with standard FVIII products. This phase III (NCT01480180), multinational, open-label, non-randomised trial evaluated the safety and clinical efficacy of N8-GP when administered for treatment of bleeds and for prophylaxis, in previously treated patients aged ≥12 years with severe haemophilia A. Patients were allocated to receive N8-GP for prophylaxis or on-demand treatment for up to 1.8 years. Patients on prophylaxis were administered one dose of 50 IU/kg of N8-GP every fourth day. Bleeds were treated with doses of 20–75 IU/kg. Total exposure to N8-GP in the trial was 14,114 exposure days (159 patient-years). For the prophylaxis arm (n=175), the median annualised bleeding rate (ABR) was 1.33 (interquartile range, 0.00–4.61), the mean ABR was 3.70 (95 % confidence interval 2.94–4.66) and 70 (40 %) patients had no bleeds during the trial. Across treatment arms, 83.6 % of bleeds resolved with one injection and 95.5 % with up to two injections. N8-GP had a favourable safety profile and was well tolerated. The frequency and types of adverse events reported were as expected in this population. One patient developed inhibitory antibodies against FVIII (≥0.6 Bethesda units [BU]) after 93 N8-GP exposure days. No clinically significant safety concerns were identified and N8-GP was effective for prophylaxis and treatment of bleeds in previously treated patients.
Keywords: GlycoPEGylated; recombinant factor VIII; haemostasis; safety; efficacy